The Waite Group's C++ Primer Plus, Third Edition - Prata, Stephen (Sams, 1998)
This book includes coverage of the Standard Template Library, one of the most significant additions to C++, and a topic you will have to master to be competitive in the C++ market. All the listings and examples use the new std namespace and in some of the more difficult areas, such as inheritance, the examples have been made more lucid and straight-forward. Also included is coverage of the latest object-oriented programming techniques such as UML, CRC cards and design patterns. TWG's C++ Primer Plus, Third edition makes understanding and experimenting with important object-oriented programming concepts like classes, inheritance, templates, and exceptions both interesting and manageable. It shows how to handle input and output, make programs perform repetitive tasks, manipulate data, hide information, use functions, and build flexible, easily modifiable programs.